Hasan al-Banna and Ikhwanul Muslimin’s Da’wah Movement in Egypt - Gumilar, Setia; Noor, Firman Maulana (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2022)
This study aims to explain the ability of the Ikhwanul Muslimin in mobilizing and framing their da’wah movement. The research was conducted by analyzing the concept of Hasan al-Banna’s da’wah movement and its impact on the existence of the Ikhwanul Muslimin’s da’wah movement. This study uses a qualitative method with a Social Movement Theory approach. This research seeks to explain the ability of the IM in mobilizing and framing its da’wah movement to maintain its existence against various resistances. The results of this study indicate that three important factors have caused the IM to maintain its existence until now, namely Internal Organizational Solidity, External Community Support, and the Moderation of the Ikhwanul Muslimin. With these three factors, the IM has become a modern Islamic organization that can withstand various pressures both from within the country and from outsiders.